Internal Control System (ICS) and Municipal Management in the Paucará District, Huancavelica, 2022 - Quispe Sullcaray, Yoni (2024)
It is important to note that the implementation of the Internal Control System (ICS) in local government is essential, as it contributes to the development of transparent, efficient, and effective management in public entities of the State. In this context, the objective of this study was to establish the relationship between the Internal Control System (ICS) and municipal management in the Paucará district, Huancavelica, 2022. The type of research was correlational, non-experimental design, and cross-sectional, with the Paucará Municipality as the object of study. The survey technique and questionnaire were used for data collection. The study population consisted of 85 civil servants and the sample consisted of 70 civil servants who perform administrative work in the Paucará Municipality. The idea was to prove that there was a meaningful relationship between the variables analyzed, so that an optimal ICS would correspond to an effective municipal management. Although this relationship was significant only for two of the three ICS dimensions, in general, it has been confirmed that there is a meaningful relationship between the ICS and municipal management in the Paucará district Municipality, Huancavelica, 2022.